GW4064 Alters Gut Microbiota Composition and Counteracts Autism-Associated Behaviors in BTBR T+tf/J Mice - Liu, Jiayin; Liu, Chuanqi; Gao, Zhanyuan; Zhou, Lianyu; Gao, Junwei; Luo, Yi; Liu, Tianyao; Fan, Xiaotang (Frontiers in Cellular and Infection Microbiology, 2022)
Autism spectrum disorder (ASD) is considered a heterogeneous neurodevelopmental disorder characterized by significant social, communication, and behavioral impairments. The gut microbiota is increasingly considered a promising therapeutic target in ASD. Farnesoid X receptor (FXR) has recently been shown to modulate the gut microbiota. We hypothesized that FXR agonist GW4064 could ameliorate behavioral deficits in an animal model for autism: BTBR T+Itpr3tf/J (BTBR) mouse. As expected, administration of GW4064 rescued the sociability of BTBR mice in the three-chamber sociability test and male-female social reciprocal interaction test, while no effects were observed in C57BL/6J mice. We also found that GW4064 administration increased fecal microbial abundance and counteracted the common ASD phenotype of a high Firmicutes to Bacteroidetes ratio in BTBR mice. In addition, GW4064 administration reversed elevated Lactobacillus and decreased Allobaculum content in the fecal matter of BTBR animals. Our findings show that GW4064 administration alleviates social deficits in BTBR mice and modulates selective aspects of the composition of the gut microbiota, suggesting that GW4064 supplementation might prove a potential strategy for improving ASD symptoms.